The generalization of the results of research of dynamic bearing capacity of hydrodynamic thrust bearings - Сидорика, Игорь Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of traditional and developed calculation methods of dynamic bearing capacity of hydrodynamic thrust bearings of various technical systems was conducted. Due to generalization of existing data and the results of the research, it was found that each of the operational factors, affecting the TB reduces its dynamic load capacity. The combined impact of these factors can deplete the dynamic load capacity of the thrust assembly and lead to the destruction of the lubricating layer, which will cause the breakdown of the TB and the failure of the technical system. This problem is particularly acute nowadays because of an increase in service life of ship machinery and a decrease in the number of planned preventive maintenance. The mathematical model was developed and calculation method of the dynamic bearing capacity of the thrust assemblies of fluid friction, which allows to determine the allowable amplitude of forced longitudinal vibrations of the shaft, face motion variation of thrust collar and allowable misalignment of the bearing housing was improved. At the design stage, improved calculation method allows to perform vibration calculations to assess the dynamic bearing capacity of the TB of various technical systems.